Aspectos contábeis-financeiros da conversão da dívida externa em investimento: estudo de casos - Carvalho, Fatima Alves de (1989)
The objective of the exploratory study was to investigate the financial accounting aspects related to the capitalization process of enterprises through resources proceeding from the Brazilian foreign debt equity conversion . Seeking to know the motives of the captivation and the resource utilizations of the debt equity conversion, the degree of modification that occurred in the financial leverage after the utilization of these resources and the manner enterprises attested receiving them in financial reports. (Chapter I). The literature revision sought to contexture the foreign debt equity conversion. In addition, related subjects to capital structure of an enterprise and accounting disclosure were approached . (Chapter II) The research method was case study. As research instruments, the questionary and the examination of the financial reports were used. (Chapter III) The researched cases were described separately. (Chapter IV), subsequently the results were analysed. Chapter V). Finally, the summary and the research conclusions are presented based on the theoretical foundations. Recommendations and suggestions for future researches are formulated. (Chapter VI).